Urolithiasis in a captive Siberian chipmunk (Eutamias sibiricus) - Kohutova, Silvia; Jekl, Vladimir (The Journal of veterinary medical science, 2021)
This clinical case describes struvite urolithiasis in a pet chipmunk. Physical examination revealed the presence of two ovoid palpable masses in the caudal part of the abdomen, which were later confirmed by radiography as urinary bladder stone. The animal underwent ventral midline laparotomy and uroliths were successfully removed. Uroliths analysis revealed the presence of struvite and bacteriology showed the presence of Proteus mirabilis. Little is known about aetiology and incidence of urolithiasis in chipmunks. Client education about husbandry, dietary needs, and animal behaviour is necessary, especially when dealing with less commonly kept exotic companion mammals. This is the first report of struvite urolithiasis in a pet chipmunk.
Keywords: haematuria; struvit; chování zvířat; Struvite; chipmunk; urolith; zvířata; struvite; Proteus mirabilis; Urolithiasis; Rodent Diseases; urolitiáza; nemoci hlodavců; fosfáty; rodent; Sciuridae; Animals; Behavior, Animal; Phosphates